A imagem fotográfica como ferramenta pedagógica na educação ambiental crítica diante dos objetivos de desenvolvimento sustentável - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2025)
This study investigates the effectiveness of photography as a pedagogical tool in environmental education, aiming to promote critical awareness of environmental issues. Concern for environmental issues is a responsibility shared by an entire generation, not limited to the individual scope. It is essential to seek solutions to reduce environmental impact and improve quality of life. In this context, Environmental Education is essential in shaping conscious and critical individuals. The goal is to explore how photography can assist in understanding and engaging students with environmental sustainability. The adopted methodology includes a qualitative approach with a case study, using photographic workshops in selected schools to collect data through observations, interviews, and visual content analysis. The research conducted a practical activity involving an image reading with undergraduates from the Biological Sciences course at the State University of Ponta Grossa. The results were analyzed by applying the discursive textual analysis proposed by Moraes and Galiazzi, which consists of the steps of Unitarization, Categorization, and Metatext. These steps were used to interpret and compare pre- and post-theory readings based on Silva and Neves' proposal. The principal authors of this research were Santaella, Dondis, Joly, Panofsky, Silva and Neves, who discuss visual language and teaching. As a didactic resource, the results indicate that photography enhances students' perception and critical reflection on the environment, facilitating the internalization of sustainability concepts. The final considerations highlight photography not only as a means of artistic expression but as a valuable tool in environmental education, capable of significantly contributing to developing critical environmental awareness among young people.
Keywords: Desenvolvimento Sustentável; Educação Ambiental Crítica; Ensino de Ciências; Imagem Fotográfica; Educação